PENGALAMAN KOMUNIKASI PEKERJA LADIES COMPANION DIKOTA PEKANBARU - Afif Fajar Risman; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Ladies Companion workers was an profession that is happening at Pekanbaru. Ladies Companion workers identic with sexy outfit and considered as one of deviate work. Based on mottive, meaning and communication experience of ladies companion workers explain how they work. Purpose of this research is to known their mottive, self meaning and how their communication experience when they do their work.This research using qualitative method with phenomenology approach. The informan consisted of 5 people as ladies companion workers using snowball sampling thecnique. Data collection using observation participant, deep interview and documentation. This research using interactive data analisys that include 3 phase which is data reduction, data presentation, and taking conclusion.The result of this research shown that their mottive to work as ladies companion is because mottive which is hobbies, broken home, economic factor and life costs. In oreder mottive is to get additional income, looking for better life. Self meaning of this ladies companion that for them this work can help their economic side. Identic with outfit and menor makeup. Ladies companion considered as deviate work. Communication experience their get is pleasure  (positive) and nunpleasure (negative). Pleasure experience which is get some bonus, get complement from their guests, advise to each other. In other side their unpleasure some kind of unpleasure treatment, sexual harrasment and considered as sex workers. After any category that found from ladies companion is Ladies companion and their Mami, as a stage for ladies companion workers.